Stresses Distribution in a Magneto-Thermoelastic Medium with Cylindrical Hole - Chand, D. (Engineering Transactions, 1997)
The distributions of elastic and thermal stresses in a thermally and electrically conducting infinitely extended homogeneous isotropic medium with a cylindrical hole, in the presence of uniform magnetic field, have been studied due to: (i) step in stress with zero temperature change and (ii) - step in temperature with zero stress at the boundary of the hole, in the context of the generalised theory of thermoelasticity. The Laplace transform technique has been used to obtain the small time solutions. As the "second sound" effects are of short duration, so the small time approximations have been considered. The standard results obtained have also been discussed at the wavefronts. The jumps and their particular cases obtained theoretically have been computed numerically and are represented graphically for carbon steel material.